PERBANDINGAN PENGAMBILAN MINYAK ATSIRI DAUN BELUNTAS DENGAN MENGGUNAKAN METODE MICROWAVE-ASSISTED EXTRACTION (MAE) DAN MICROWAVE ASSISTED HYDRO-DISTILLATION (MAHD) - Nadya Lituhayu; Bintang Nirtara Firmansyah; Fitri Icha Oryza Sativa; Muyassaroh (Teknik Kimia ITN Malang, 2024)
Indian pluchea leaf is one of the medicinal plants included in the essential oil group that is not traded in Indonesia, even though it has flavonoid levels that are useful, especially in the health industry. For this reason, research related to the process of extracting beluntas essential oil is still limited. The use of microwaves is considered to extract essential oil better and faster. This study aims to compare modern extraction methods, namely MAE (Microwave-Assisted Extraction) and MAHD (Microwave Assisted Hydro-Distillation) using different solvents. Other variables used in this study were drying method and microwave power. The results showed that the best results in the use of MAHD method with oven drying type and Microwave power of 300 watts which produced flavonoid content of 3.64%